Prevalence and Molecular Characteristics of Extended-Spectrum β-Lactamase Genes in Escherichia coli Isolated from Diarrheic Patients in China - Bai, Li; Wang, Lili; Yang, Xiaorong; Wang, Juan; Gan, Xin; Wang, Wei; Xu, Jin; Chen, Qian; Lan, Ruiting; Fanning, Séamus; Li, Fengqin (Frontiers in Microbiology, 2017)
ABSTRACT Backgroud: The emergence and spread of antimicrobial resistance has become a major global public health concern. A component element of this is the spread of the plasmid-encoded extended-spectrum β-lactamase (ESBL) genes, conferring resistance to third-generation cephalosporins. The purpose of this study was to investigate the molecular characteristics of ESBL-encoding genes identified in Escherichia coli cultured from diarrheic patients in China from 2013 to 2014. Methods: A total of 51 Escherichia coli were confirmed as ESBL producers by double-disk synergy testing of 912 Escherichia coli isolates studied. Polymerase chain reaction (PCR) and DNA sequencing were performed to identify the corresponding ESBL genes. Susceptibility testing was tested by the disk diffusion method. Plasmids were typed by PCR-based replicon typing and their sizes were determined by S1-nuclease pulsed-field gel electrophoresis. Multi-locus sequence typing (MLST) and phylogrouping were also performed. Broth mating assays were carried out for all isolates to determine whether the ESBL marker could be transferred by conjugation. Results: Of the 51 ESBL-positive isolates identified, blaCTX-M, blaTEM, blaOXA and blaSHV were detected in 51, 26, 3, 1 of these isolates respectively. Sequencing revealed that 7 blaCTX-M subtypes were detected, with blaCTX-M-14 being the most common, followed by blaCTX-M-79 and blaCTX-M-28. Of the 26 TEM-positive isolates identified, all of these were blaTEM-1 genotypes. All isolates contained one to three large plasmids and ten replicon types were detected. Of these, IncFrep (n = 50), IncK/B (n = 31), IncFIB (n = 26), IncB/O (n = 14), and IncI1-Ir (n = 8) replicon types were the predominating incompatibility groups. Twenty-six isolates demonstrated the ability to transfer their cefotaxime resistance marker at high transfer rates. MLST typing identified 31 STs and phylogenetic grouping showed that twelve of the 51 donor strains belonged to phylogroup B2. Conclusions: This study highlights the diversity of the ESBL producing E. coli and also the diversity of ESBL genes and plasmids carrying these genes in China, which poses a threat to public health.